Media Power and Democratization in Brazil: TV Globo and the Dilemmas of Political Accountability - Porto, Mauro (Taylor & Francis, 2012)
This book analyzes the relationship between media power and democratization in transitional societies based on a case study about TV Globo, Brazil's largest media group.
OCLC: 1120933349
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé

Structural Changes in the Ibero-American TV Market: Concentration and Convergence against Diversity? - Mastrini, Guillermo; Leiva, María Trinidad García (The Routledge Companion to Global Television, 2019)
This chapter examines the structural changes that can be identified in Ibero-American television in the first 15 years of the 21st century. Taking as a reference the main TV markets in the region (Mexico, Brazil, Argentina and Spain) and their peculiar historical developments, a brief introduction and overview describes their characteristics, potentials and limitations, underlining their strengths, weaknesses and challenges. The analysis, framed in the globalizing phase that cultural products and services are undergoing jointly with their increased digitization, suggests two fundamental drivers of change, summarized in the notions of concentration and convergence. To conclude, policies and recommendations for action are explored, with a view to promote and protect audiovisual diversity.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Argentine (corpus analysé); Argentine (lieu de production du savoir); Brésil (corpus analysé); Espagne (corpus analysé); Espagne (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Venezuela : Fiction in the Dark - Alvarado, Morella; Torrealba, Luisa (Obitel 2020: Melodrama in Times of Streaming, 2020)
During 2019, various situations once again showed the deep crisis in the country. Audiovisual production continued, albeit with figures that account for a declining industry. Four productions were released: a first was made by the state channel (TVe), a second by a local independent producer (Oduver Cubillán and BGcreativos), the third was produced by the private channel (RCTV) and broadcast by the subscription channel IVC Networks, and the fourth was also produced by RCTV. While the first two productions did not exceed the 35-episode figure, the third and fourth had 73 episodes. On March 7, there was the biggest blackout in the country’s history. For more than a week, 95% of the territory was paralyzed by a lack of electricity. The action was classified by the government as an electric sabotage. The darkness that covered the country also subsumed serial fiction.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Venezuela (corpus analysé); Venezuela (lieu de production du savoir); _Nettoyé

Uruguay: Ibero-American Fiction Loses Ground to Entertainment - Sánchez Vilela, Rosario; Gadea, Lucia (Obitel 2020: Melodrama in Times of Streaming, 2020)
A look at the screens of Uruguay’s open television in prime time will give the viewer a very reduced offer: after a television newscast that exceeds two hours long, there are only contest pro- grams, national or imported ones. It is possible that in the afternoon and at night the viewer finds a telenovela, almost always Turkish one. This is a very different panorama from the Uruguayan televi- sion history. Ibero-American fiction is in decline on open television, while its offer on VoD expands. In this chapter we will try to consider the various aspects of this landscape. Melodrama is on both options, open television and streaming, on a broad thematic spectrum, even in productions that are not usually classified as such. In the absence of national fiction in the period, at the end of the chapter we will study the melodrama in prison fiction, particularly in the case of El Marginal.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Uruguay (corpus analysé); Uruguay (lieu de production du savoir); _Nettoyé

Peru: Social Issues and Comedy in Fiction - Cassano, Giuliana; Vásquez, Guillermo; Dettleff, James A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
The country’s political crisis led to the confrontation between the Peruvian Congress and President Martín Vizcarra on irreconcil- able limits. After a second denial of confidence, Vizcarra made use of his constitutional prerogatives and dissolved Congress at the end of September 2019. The majority of the mass media step in line with the different positions of the Executive or the opposition, giv- ing much more attention to the political situation, thus modifying the TV programing. In this scenario, the Enfoca group – owner of Latina station – has continued looking for potential buyers, but without success yet. The conglomerate – with interest in financial, health and productive sectors – does not feel that the investment made in acquiring all the station’s shares seven years ago yielded the expected results. Meanwhile, Willax – a small locally held station acquired by the Wong group in 2015 with promises of a large investment – has become a stronghold of opposition to the government of Vizcarra and the largest broadcaster of Korean fictions. In February 2020, they an- nounced that a commercial partnership had been signed with South Korean company CJ ENM, a production company of several Korean dramas and the award-winning film Parasite, but without indicating what this company could mean for audiovisual production in Peru.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Pérou (corpus analysé); Pérou (lieu de production du savoir); _Nettoyé

Colombia: Melodrama Lives in Times of Streaming - Díaz, Fernando Aranguren; Bohórquez, Borys Bustamante; Riveros Solórzano, Hernán Javier (Obitel 2020: Melodrama in Times of Streaming, 2020)
The year 2019 in Colombia was characterized by the presence of a series of social and cultural phenomena of high impact on the population, such as the National Strike on November 21, when dif- ferent sectors expressed their disagreement with the country’s poli- cies and the reforms that were being proposed for the new year. This situation led to a leading presence of the news on the small screen and, at the same time, an interesting reflection of national identity, the needs of various Colombian social groups and the cul- tural matrices of the nation. In this hectic context and in accordance with a certain global climate of crisis in democratic and government systems, a highly interesting television phenomenon emerges: the highly successful reappearance of the programs that marked differ- ent generations of compatriots and that, as in the past, once again led families to discuss episodes and situations presented under the classical structure of melodrama.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); Colombie (corpus analysé); Colombie (lieu de production du savoir); _Nettoyé

Brazil: Time of Brazilian Streaming - Vassallo de Lopes, Maria Immacolata; Prezia Lemos, Ligia (Obitel 2020: Melodrama in Times of Streaming, 2020)
In 2019, the World Wide Web (www) celebrated its 30th anni- versary, However, the internet had not yet asserted itself as a right in the “network society” (Castells, 2009), and its balance points to the expansion of both opportunities and threats. Another fact that deserves to be highlighted in the year was the drop in the rating as a global phenomenon that challenges the television industry. It means change of habits and search for new business models. The integration of platforms and the generation of quality content appear as pillars of thetransformation of audiovisual worldwide. And the changes are manifested with a certain degree of diversity, according to the economic and cultural characteristics of each society, with disruptive processes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé

Argentina: The Fall of Open TV Continues: Production Companies Bet on Platforms with Themes Regarding Marginality and Corruption - Aprea, Gustavo; Kirchheimer, Mónica S.; Rivero, Ezequiel A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
Serial fiction released in Argentina in 2019 continues to fall. Only one telenovela had more than 200 chapters. To a lesser extent than the previous year, the supply of serialized fiction incorporated themes from the social agenda, especially feminist struggles and the visibility of sexual dissidence. The channels found in the co-produc- tion and in the production for platforms one of the ways in which fic- tion survives. Some of these programs are now on the open television screen. New fiction releases from Ibero-America are also falling.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Argentine (corpus analysé); Argentine (lieu de production du savoir); _Nettoyé

Introduction: Ibero-American Fiction in the Midst of Political and Technological Changes: the Persistence of Melodrama as a Narrative Matrix - Aprea, Gustavo; Kirchheimer, Mónica S.; Rivero, Ezequiel A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
This year, the Ibero-American Observatory of Television Fic- tion (Obitel) has dedicated special attention to the persistence of melodrama on screens in times of streaming and the proliferation of deprogrammed and multiscreen consumption. Obitel is made up of 12 countries that monitor the production and distribution of televi- sion fiction. For this yearbook, however, it was not possible to count on the participation of Ecuador, since it did not achieve the neces- sary conditions to work with the common methodology required. Chile, for its part, participated by providing data in order not to in- terrupt the historical series, but the analytical chapter corresponding to that country is not included either.
Keywords: 1-TV; 2-Étude des industries culturelles; 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Argentine (lieu de production du savoir); _Nettoyé

“Estética(s) decolonial(es)1”: entrevista a Pedro Pablo Gómez - Vasquez, Angélica González; Zacarias, Gabriel Ferreira (Estudios Artísticos, 2016)
En esta conversación se indaga por la cuestión decolonial de la estética, sus puntos de origen históricos y geográficos, además de sus posibilidades en el contexto de reconfiguración actual del orden mundial. Desde esta perspectiva, se pretende aclarar en qué consiste la opción decolonial, respecto de otras opciones, sin olvidar cuestiones importantes del arte, la historia, el museo, la curaduría y sus implicaciones éticas, políticas y epistémicas. Cette conversation touche à la question de l’esthétique décoloniale, de ses points d’origine historiques et géographiques et de ses possibilités dans le contexte de la reconfiguration actuelle de l’ordre mondial. Dans cette perspective, l’objectif est de clarifier l’option décoloniale par rapport à d’autres options — sans oublier les questions importantes de l’art, de l’histoire, des musées, de la mission du curateur — et ses implications éthiques, politiques et épistémiques.
Texte en français : https://journals.openedition.org/marges/1207
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave Macmillan, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Telenovelas and Transformation: Saving Brazil's Television Industry - Svartman, Rosane (Routledge, Taylor & Francis Group, 2021)
"This book investigates how telenovelas may be the key to the future of Brazilian television and how this content can survive in an interconnected media landscape. Recognised writer and scholar Rosane Svartman considers the particular characteristics of the telenovela format - number of episodes, melodrama influence, and influence of the audience on future writing - to explore how these can be preserved on multimedia platforms, and the challenges this change may present. Svartman further charts the transformations of the telenovela throughout its history and its major influences and unveils the main storytelling elements and writing processes. Chapters examine the business model of Brazilian corporate television within the current context of hypermedia and analyse how this relationship evolves as it is influenced by the new interactive tools and technologies that amplify the audience's power. Merging empirical practices and theory, this book will be of great interest to scholars and students of transmedia storytelling, television studies, and Latin American media, as well as professionals working in these areas"– Provided by publisher.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé